.. _gimbal-lock: ============= Gimbal lock ============= See also: http://en.wikipedia.org/wiki/Gimbal_lock Euler angles have a major deficiency, and that is, that it is possible, in some rotation sequences, to reach a situation where two of the three Euler angles cause rotation around the same axis of the object. In the case below, rotation around the $x$ axis becomes indistinguishable in its effect from rotation around the $z$ axis, so the $z$ and $x$ axis angles collapse into one transformation, and the rotation reduces from three degrees of freedom to two. Imagine that we are using the Euler angle convention of starting with a rotation around the $x$ axis, followed by the $y$ axis, followed by the $z$ axis. Here we see a Spitfire aircraft, flying across the screen. The $x$ axis is left to right (tail to nose), the $y$ axis is from the left wing tip to the right wing tip (going away from the screen), and the $z$ axis is from bottom to top: .. image:: images/spitfire_0.png Imagine we wanted to do a slight roll with the left wing tilting down (rotation about $x$) like this: .. image:: images/spitfire_x.png followed by a violent pitch so we are pointing straight up (rotation around $y$ axis): .. image:: images/spitfire_y.png Now we'd like to do a turn of the nose towards the viewer (and the tail away from the viewer): .. image:: images/spitfire_hoped.png But, wait, let's go back over that again. Look at the result of the rotation around the $y$ axis. Notice that the $x$ axis, as was, is now aligned with the $z$ axis, as it is now. Rotating around the $z$ axis will have exactly the same effect as adding an extra rotation around the $x$ axis at the beginning. That means that, when there is a $y$ axis rotation that rotates the $x$ axis onto the $z$ axis (a rotation of $\pm\pi/2$ around the $y$ axis) - the $x$ and $y$ axes are "locked" together. Mathematics of gimbal lock ========================== We see gimbal lock for this type of Euler axis convention, when $\cos(\beta) = 0$, where $\beta$ is the angle of rotation around the $y$ axis. By "this type of convention" we mean using rotation around all 3 of the $x$, $y$ and $z$ axes, rather than using the same axis twice - e.g. the physics convention of $z$ followed by $x$ followed by $z$ axis rotation (the physics convention has different properties to its gimbal lock). We can show how gimbal lock works by creating a rotation matrix for the three component rotations. Recall that, for a rotation of $\alpha$ radians around $x$, followed by a rotation $\beta$ around $y$, followed by rotation $\gamma$ around $z$, the rotation matrix $R$ is: .. math:: R = \left(\begin{smallmatrix}\operatorname{cos}\left(\beta\right) \operatorname{cos}\left(\gamma\right) & - \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) + \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\beta\right) & \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) + \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\beta\right)\\\operatorname{cos}\left(\beta\right) \operatorname{sin}\left(\gamma\right) & \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) + \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\beta\right) \operatorname{sin}\left(\gamma\right) &- \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) + \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\beta\right) \operatorname{sin}\left(\gamma\right)\\- \operatorname{sin}\left(\beta\right) & \operatorname{cos}\left(\beta\right) \operatorname{sin}\left(\alpha\right) & \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\beta\right)\end{smallmatrix}\right) When $\cos(\beta) = 0$, $\sin(\beta) = \pm1$ and $R$ simplifies to: .. math:: R = \left(\begin{smallmatrix}0 & - \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) + \pm{1} \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) & \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) + \pm{1} \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right)\\0 & \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) + \pm{1} \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) & - \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) + \pm{1} \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right)\\- \pm{1} & 0 & 0\end{smallmatrix}\right) When $\sin(\beta) = 1$: .. math:: R = \left(\begin{smallmatrix}0 & \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) - \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) & \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) + \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right)\\0 & \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) + \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) & \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) - \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right)\\-1 & 0 & 0\end{smallmatrix}\right) From the `angle sum and difference identities `_ (see also `geometric proof `_, `Mathworld treatment `_) we remind ourselves that, for any two angles $\alpha$ and $\beta$: .. math:: \sin(\alpha \pm \beta) = \sin \alpha \cos \beta \pm \cos \alpha \sin \beta \, \cos(\alpha \pm \beta) = \cos \alpha \cos \beta \mp \sin \alpha \sin \beta We can rewrite $R$ as: .. math:: R = \left(\begin{smallmatrix}0 & V_{1} & V_{2}\\0 & V_{2} & - V_{1}\\-1 & 0 & 0\end{smallmatrix}\right) where: .. math:: V_1 = \operatorname{cos}\left(\gamma\right) \operatorname{sin}\left(\alpha\right) - \operatorname{cos}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) = \sin(\alpha - \gamma) \, V_2 = \operatorname{cos}\left(\alpha\right) \operatorname{cos}\left(\gamma\right) + \operatorname{sin}\left(\alpha\right) \operatorname{sin}\left(\gamma\right) = \cos(\alpha - \gamma) We immediately see that $\alpha$ and $\gamma$ are going to lead the same transformation - the mathematical expression of the observation on the spitfire above, that rotation around the $x$ axis is equivalent to rotation about the $z$ axis. It's easy to do the same set of reductions, with the same conclusion, for the case where $\sin(\beta) = -1$ - see http://www.gregslabaugh.name/publications/euler.pdf.